Analisis Tahanan Isolasi Peralatan Utama Gardu Induk Panakkukang - Fandi Rahman; Muh. Fitrah; Suryani Suryani; Hafsah Nirwana (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
This study aims to find out about the procedure for measuring the isolation resistance of the main equipment of the 150 kV conventional substation (AIS) as many as 5 bays at the Panakkukang Substation through the measurement of the insulation resistance value in accordance with the predetermined standards. The method used in this study is quantitative descriptive. The subject of the study to be studied is a comparison of isolation resistance values in pre- and post-treatment. This was done to find out if there was a change in the insulation resistance value of the main equipment of the Substation. The main equipment studied is LA, PMT, CT, VT, and Transformer. Measurements were taken with a Megger measuring instrument, with a voltage injection of 5kV. For 5kV voltage injection, the maximum value of the test device is >1000 GΩ. The standard used is IEEE 43-2000, which is > 1 MΩ / 1 kV. Based on the results of research that has been carried out on each main equipment of the substation at GI Panakkukang. It can be concluded that the isolation resistance value in each main equipment of the substation at GI Panakkukang is above the minimum value (> MΩ/1 KV) in accordance with the IEEE Std 62: 1995 standard, VDE Catalogue 228/4, and the standard used by PLN in the "Power System Maintenance Guidebook" in 2014 the isolation resistance value at each main substation at GI Panakkukang has increased after being maintained. Maintenance can be carried out by cleaning the equipment body and foreign materials, and measuring the insulation resistance periodically.